PENGARUH KESELAMATAN DAN KESEHATAN KERJA TERHADAP KEPUASAN KERJA PADA PT. PANDAWA SURYA SENTOSA DI KOTA BALIKPAPAN, KALIMANTAN TIMUR - Suryawan, Kadek Senli Bonix; Pio, Riane; Rumawas, Wehelmina (Sam Ratulangi University, 2018)
The purpose of this study was to determine the effect of work safety and occupational health on jobsatisfaction at PT. Pandawa Surya Sentosa in Balikpapan City, East Kalimantan. This research uses aquantitative approach. The subjects of this study were 107 employees selected using random samplingtechnique. Data collection methods used is the scale of work safety, occupational health and jobsatisfaction. The collected data were analysed using multiple linear regression analysis using theStatistical Package for Social Sciences (SPSS) program for Windows 24.0.The results of the study with a confidence level of 95% showed that: (1) there was no effect of work safetyon job satisfaction can be shown based on the t test that the value of count 0.101 < t table 1,983 and thevalue Sig 0,919 > 0,05, and Î² = 0,009; (2) there is a work health effect on job satisfaction can be shownbased on the t test that the value of count 4.191 > t table 1,983 and the value of Sig 0,000 < 0,05, and Î² =0,009; (3) Based on the results of the f test, that the F count > F table (8.782> 2.30) with a significant0.000 <0.05, this means that the independent variables (X1) and (X2) simultaneously have a significantpositive effect on employee job satisfaction at PT. Pandawa Surya Sentosa in Balikpapan City, EastKalimantan.Keywords: Work Safety, Occupational Health, Job Satisfaction